Pretreatment elevated mean corpuscular volume as an indicator for high risk esophageal second primary cancer in patients with head and neck cancer. Issue 3 (June 2023) - Tsushima, Nayuta; Kano, Satoshi; Suzuki, Takayoshi; Hamada, Seijiro; Homma, Akihiro
Abstract: Objective: Esophageal cancer is the most common second primary cancer (SPC) in patients with head and neck cancer (HNC). Esophageal SPC has a negative impact on survival. Elevated mean corpuscular volume (MCV) is an accepted predictor of esophageal cancer risk. The aim of this study was to elucidate the usefulness of elevated MCV as an indicator of a high risk for esophageal SPC. Methods: We retrospectively reviewed the medical records of patients with oropharyngeal, hypopharyngeal, and laryngeal squamous cell carcinoma who underwent chemoradiotherapy between 2003 and 2012. We excluded patients younger than 20 years or who had received treatment for esophageal cancer and who had a histologically unproven lesion. Patients were divided into two groups according to their MCV. The cut-off for MCV was defined by receiver operating characteristics curve analysis. The primary endpoint was the cumulative incidence of esophageal SPC. Results: A total of 295 patients were included. The median follow-up period for surviving patients was 7.4 years and the optimal cut-off point was 99.0 fL. One hundred ninety-five patients (66%) had an MCV < 99.0 fL and 100 (34%) had an MCV ≥ 99.0 fL. The 5-year cumulative incidence in patients with an MCV < 99.0 fL and ≥ 99.0 fL was 8.7% and 27%, respectively. In the multivariate analysis, an MCV ≥ 99.0 fL (HR=2.2; 95%CI, 1.1-4.2) was an independent risk factor. Conclusion: MCV ≥ 99.0 fL was found to be a risk factor for esophageal SPC. We, therefore, recommend that patients with an MCV ≥ 99.0 fL should undergo intensive monitoring.